(untitled) (Journal of Human Sciences, 2022)
The study actuly hed light on gclentif aspects of imamate ,abusaid abdelsam ben said ben habeb altakoukhythe great imamateof marocco who is called “sahnon “ and who wrote trie “greatcorpus “ , and is one the fullowcrs of imamate “malik “, and who spre ad that believe in “240 h “ he have study under famous scholars like ben abi kharija , bahlol ,ali ben ziad ,ben hassan , ben ashras , and khanem. He followed their schooi and become as one of them , he was so famous in morocco , and he teached many greduntss until he died in year “one hundred and eighty seven “ he was very keen when supervised judgeship he was succecded by his son ,and sback ben khalil , saed ben nemer, and abdulla ben ghafek , mohamed ben abdulla ben abdoss , wahab ben nafie and many other scholar of jursiprudance ,and he was so famous thnt few of scholars rechead his prestnge.